Application of spatial statistics in the analysis of European funds usage in provinces in Poland - Warzecha, Katarzyna; Wójcik, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
This paper carried out a statistical analysis of projects co-financed by the Structural Funds in the years 2004-2013. The analysis was conducted in terms of regions. In particular, provinces had different priorities in terms of content projects co-financed by the European Funds. This is due to the different geographical location, degree of urbanization and population density of each subregion. This paper verifies the hypothesis of the existence of neighboring provinces, which obtain subsidies at the approximate level from European funds for the projects executing specific aims. The use of spatial statistics allows to investigate the existence of spatial dependence for the studied regions thanks to the use of European funds
Mathematical Economics, 2016, Nr 12 (19), s. 61-81
Keywords: European funds; global and local Moran's I statistics; spatial analysis